Evaluation of quality and bioactivity of lipid extracted from sardine (Sardinella spp.) processing wastes by enzymatic hydrolysis - Ganancias, Cindy Ravelo (2023.)
Fish and its processing wastes are known source of omega-3 polyunsaturated fatty acids (PUFAs), which has gained popularity due to their reported benefits in cardiovascular-related diseases and overall health. However, traditional oil extraction methods use high temperatures and toxic solvents, which can diminish the biological activities of the lipids and may be carcinogenic for humans. In this study, enzymatic hydrolysis using the enzyme Alcalase for the recovery of oil from the processing wastes of sardines (Sardinella spp.) was conducted. Optimization of hydrolysis conditions was carried out using the central composite design of response surface methodology with three independent variables: hydrolysis time (h), enzyme concentration (%), and temperature (℃). The suggested optimum conditions were 3 h, 0.80%, and 57.5 ℃, which obtained an oil yield of 8.74% ± 0.12. After the oil extraction, refining was done to improve the quality of the crude oil to possibly suit different applications in various industries. The refining process enhanced the quality parameters of the extracted oil such as the peroxide value, thiobarbituric acid reactive substances, free fatty acid, fatty acid profile, and colorimetric parameters, without compromising the PUFA content. approximately52-59% of the eicosa pentaenoic acid and docosa acid were concentrated after oil refinign. Furthermore, the refined oil exhibited considerable antioxidant and anti-inflammatory activities with 2,2-diphenyl-1-picrylhydrazyl scavenging activity of 23.47 - 55.97%, cyclooxygenase-2 inhibition of 26.38 - 81.94 %, 5 lipoxygenase inhibition of 22.51 - 70.41 %, and protein denaturation inhibition of 34.9 - 89.6 %. Therefore, the present study demonstrated the potential recovery of functional oil from the processing wastes of sardines suggesting a sustainable approach to waste valorization.
Thesis (MS Fisheries -- Fish Processing Technology). -- [Miagao, Iloilo] : University of the Philippines Visayas, December 2023.